Comparative study of milk somatic cells count (SCC) in cows, sheep and goats in summer and winter in Baghdad - Abood, A. S. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was included a collection of 90 milk samples from 30 cows ,30 ewe , and 30 does ,in mid-term of lactation period , 15 samples collected during summer and 15 samples duringwinter for each other . All samples were subjected to microscopical examination after staining with Newman Limbert stain , to check : The mean number of SCC in cows was ( 426.600 ) cells / ml through the summer , while the mean number of SCC in the winter ( 893.300) cells / ml . The number of SCC in sheep samples were estimated (287.300) cells / ml in summer, and (980.000 ) cells / ml in winter . while the goat were given mean( 533.300) cell / ml in summer and ( ( 933.300) cell / ml in winter . This study gives the difference in milk quality between season and species ( cow , sheep , and goat ) . Statistical analyses gives significant ( p < 0.05 ) between summer and winter in all species .